2013
DOI: 10.1039/c3sm50832c
|View full text |Cite
|
Sign up to set email alerts
|

Diffusivities, viscosities, and conductivities of solvent-free ionically grafted nanoparticles

Abstract: A new class of conductive composite materials, solvent-free ionically grafted nanoparticles, were modeled by coarse-grained molecular dynamics methods. The grafted oligomeric counterions were observed to migrate between different cores, contributing to the unique properties of the materials. We investigated the dynamics by analyzing the dependence on temperature and structural parameters of the transport properties (self-diffusion coefficients, viscosities and conductivities) and counterion migration kinetics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Here, ε r denotes the effective relative dielectric constant of the composite system, which is usually deduced from the dielectric constants of the two constituents by a mixing expression such as the Maxwell-Garnett mixing rule based on an effective-medium theory [60,61]. Many non-conjugated polymers have a low relative dielectric constant, which decreases with the molecular weight and temperature, near nanosilica ε r value, thus we adopt the same ε r value, in this study, for polymers and NP fillers as in previous studies [34,35], and do not consider any φ-dependence of the effective ε r . Our choice for ε r will be discussed further below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, ε r denotes the effective relative dielectric constant of the composite system, which is usually deduced from the dielectric constants of the two constituents by a mixing expression such as the Maxwell-Garnett mixing rule based on an effective-medium theory [60,61]. Many non-conjugated polymers have a low relative dielectric constant, which decreases with the molecular weight and temperature, near nanosilica ε r value, thus we adopt the same ε r value, in this study, for polymers and NP fillers as in previous studies [34,35], and do not consider any φ-dependence of the effective ε r . Our choice for ε r will be discussed further below.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, an exceptional degree of dispersion of the silica in the polymer and high degree of order in both thin film and bulk forms was achieved [18]. For matrix-free model systems [34,35] it was observed that NPs diffuse similarly to a polymer solution [36][37][38], while chains diffuse faster than NPs [39]. Ionic interactions are also included in the case of ionomers in which the morphology and phase behavior depend on the electrostatic strength [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, fundamental research on ionic polymer nanocomposites to understand and investigate the ionic interactions, nanoparticle mobility on the interphasial region, and nanoparticle dispersion state of the nanocomposite have not been performed so far. Exceptions are the coarse grained model by Hong et al [79,80] for nanoparticle ionic liquids, where nanoparticles diffuse like in a polymer solution [81,82,83] while chains diffuse faster than nanoparticles, as well as the studies in ionomer nanocomposites [59,84], polymer charged solutions [85,86] and polymer gels [87,88].…”
Section: Introductionmentioning
confidence: 99%
“…The above open questions and issues can be addressed using molecular dynamics (MD) simulations. A few such simulations have been reported 11 14 . A common feature of these simulations is that the radius of the nanoparticles is small (~1 nm), the chain length of the polymers is short and comparable to the nanoparticle’s radius (e.g., the linear polymers used in ref.…”
Section: Introductionmentioning
confidence: 99%